Kesalahan Siswa dalam Menyelesaikan Soal Cerita: Sebuah Penelitian Meta-Ethnography - Eryn Thrisseany; Febriana Kristanti; Shoffan Shoffa (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2023)
This study intends to summarize the findings of research on word problem solving errors made by students as well as the types of errors made by students that have been increasingly prevalent in reports over the past five years. The strategy employed is a descriptive method, which entails examining current symptoms using information gathered from numerous prior research and compiled using a meta-ethnography approach. The goal of the study is to provide a report on the findings of research conducted by teachers and former mathematics education students who looked at word problem solving errors made by students. The summary's findings demonstrate that the following types of student errors are errors: Understanding definitions, applying ideas, methods, and strategies; Determining the Knowledge Aspect of Understanding and Applying Story Problems; Representing Information from Story Questions into Mathematical Sentences; 4) applying concepts to specific materials without understanding how concepts relate to one another or the significance of symbols; 5) Students in drawing conclusions about the outcomes of problem-solving or errors in writing the final solution.